A reevaluation and redescription of the branchiobdellidan Sathodrilus tetrodonta (Pierantoni, 1906) new comb. (Annelida: Clitellata) - Gelder, Stuart R. (Zootaxa, 2024)
The questionable status of Branchiobdella tetrodonta Pierantoni, 1906 is resolved and the species is transferred to the correct genus. The original description was made from specimens removed from signal crayfish collected in California, USA, unfortunately, Pierantoni (1906c) did not designate any type specimens nor where the preparations were deposited; they are now presumed lost. Holt (1967) believed B. tetrodonta possessed unique penial hooks and a chitinous sheath which was due to his mistranslation of the original Italian description. As a result, Sathodrilus attenuatus Holt, 1981, was described even though specimens came from the same area and host and possessed very similar jaw characteristics to B. tetrodonta. In addition, the jaw characteristics of both endemic species are unique in the Pacific Ocean drainage of the USA. A reassessment of the literature and re-examination of Holt’s type specimens has resulted in the species name becoming a new combination, Sathodrilus tetrodonta (Pierantoni, 1906), with Sathodrilus attenuatus Holt, 1981, as its junior synonym.